The acetylator phenotypes of Saudi Arabians with coronary arterial atheroma. Issue 3 (March 1991) - Evans, D A; Wicks, J; Higgins, J; Assisto, M
Abstract : The acetylator phenotypes were determined by means of a sulfamethazine test in 101 Saudi Arabian patients with authenticated coronary atheroma; 65 were found to be slow acetylators. This distribution of phenotypes is not significantly different from that in 220 controls, 148 of whom were slow acetylators. This finding makes it unlikely that compounds containing a primary aromatic amino or a hydrazino group are involved in the aetiology or pathogenesis of coronary atheroma.